2022
DOI: 10.1186/s40345-022-00256-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the quality, safety, and functionality of commonly used smartphone apps for bipolar disorder mood and sleep self-management

Abstract: Background Individuals with bipolar disorder (BD) are increasingly turning to smartphone applications (apps) for health information and self-management support. While reviews have raised concerns regarding the effectiveness and safety of publicly available apps for BD, apps surveyed may not reflect what individuals with BD are using. The present study had two aims: first, to characterize the use of health apps to support mood and sleep amongst people with BD, and second, to evaluate the quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 83 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…Although research-led studies have developed and evaluated mobile apps for BD, the dissemination and uptake of these apps in real-world contexts must be considered to reach the target population and maximize their impact. A recent web-based survey investigating the use of mobile apps to support mood and sleep self-management among individuals with BD found that 41.6% of participants reported using a self-management app related to mood and/or sleep [ 32 ]. The most nominated app for mood monitoring was Daylio, and the most reported app for sleep monitoring was Fitbit.…”
Section: Improving the Dissemination And Uptake Of Apps For Bdmentioning
confidence: 99%
“…Although research-led studies have developed and evaluated mobile apps for BD, the dissemination and uptake of these apps in real-world contexts must be considered to reach the target population and maximize their impact. A recent web-based survey investigating the use of mobile apps to support mood and sleep self-management among individuals with BD found that 41.6% of participants reported using a self-management app related to mood and/or sleep [ 32 ]. The most nominated app for mood monitoring was Daylio, and the most reported app for sleep monitoring was Fitbit.…”
Section: Improving the Dissemination And Uptake Of Apps For Bdmentioning
confidence: 99%
“…Whereas the influence of weight on lithium levels has been the subject of previous research (Grandjean and Lithium 2009), the influence of diet, sleep (Spano et al 2022), and physical activity has been neglected. Sleep is one of the most important lifestyle factors in BD and its regularity is used as a therapeutic tool to improve prognosis (Morton et al 2022). With respect to body size, weight is related to creatinine clearance, the most important factor related to lithium levels (ElDesoky et al 2008;Methaneethorn and Sringam 2019).…”
Section: Introductionmentioning
confidence: 99%